Towards a Maturity Model for a Reuse Incremental Adoption - Garcia, Vinicius Cardoso; Lucrédio, Daniel; Alvaro, Alexandre; Almeida, Eduardo Santana de; Fortes, Renata Pontin de Mattos; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2007: Anais do I Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de SoftwareDO - 10.5753/sbcars.2007.24119, 2007)
Software has been reused in applications development ever since programming started. However, the reuse practices have mostly been ad hoc, and the potential benefits of reuse have never been fully realized. Systematic reuse offers the greatest potential for significant gains in software development productivity and quality. Organizations are looking for ways to develop a software reuse program. The strategy for adopting a reuse technology should be based on a vision for improving the organization’s way of doing business. Thus, this paper presents a Reuse Maturity Model proposal, describing consistence features for the incremental reuse adoption.